Uji Aktivitas Inhibisi Î±-Glukosidase Isolat Bakteri Endofit Tanaman Duwet (Syzygium cumini L. Skeels) Sebagai Sumber Alternatif Antidiabetes - Fatin, Nuhaul; Pujiyanto, Sri; Raharjo, Budi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Diabetes mellitus (DM) is a metabolic disease contributes to the health problem in Indonesia. The inhibition of Î±-glucosidase is one of the mechanisms of antidiabetic treatment. Î±-glucosidase inhibitor can be found in the duwet plants (Syzygium cumini L. Skeels) Â that have been used traditionally in Indonesia as antidiabetic drug. However, due to the insufficient quantity and the long harvesting time, the forthcoming appliclation of duwet is consideraly not promising. The natural tendencies of endophytic microorganisms are identicl to the host plant. In this case the endophytic bacteria of the duwet plant is studied to determine its potential as an alternative to producing Î±-glucosidase inhibitors. A total of 14 isolates of endophytic duwet bacteria isolated tested the ability of Î±-glucosidase inhibitors using p-nitrophenyl-D-Î±-glucopyranoside. The result ofÂ the absorbance based on breakdown of substrate that produce colored product and analyzed by spectrophotometric technique. All isolates had Î±-glucosidase inhibitor activity, the highest activity produced by isolates A21 and A22 with value of 69,18% and 69,22%.Â Keywords : inhibitor Î±-glucosidase, endophytic bacteria, Syzygium cumini